About the Methodology Related to Indicating Sensitivity of Regions Marketing - Tamara Petrovna Danko; Elena Leonidovna Zarova; Leonid Aleksandrovich Bragin; Vladimir Dmitrievich Sekerin; Anna Evgenievna Gorohova (International Review of Management and Marketing, 2016)
Under the conditions when the Russian economy is moving to the world market, developing the evaluation of the competitive positioning and indicating of Russian regions becomes a key factor. We understand regions marketing as a set of products aiming at developing competitive advantages and individual peculiarities of cities and regions when positioning them on the world-wide market of territories. We will remind that region marketing is the specialized marketing activity performed on the territory for the purpose of creating, maintaining and changing opinions, intentions and behavior of subjects about it. Such subjects either already exist and operate on the specific territory or include their potential consumers. The target directions of this activity include attractiveness, total image of the territory (place), attractiveness of natural, material and technical, financial, labor, organizational, social and other resources focused on the territory, as well as opportunities to realize and reproduce such resources. This stipulates the necessity to improve the current system of statistical recording and accounting, work out a new system to evaluate competitive positioning and evaluate the sensitivity of regions marketing. Our goal was to consider the existing tools to indicate regions marketing (SRM), define the most narrow moments of researching this issue, and work out new tools for indicating as well as to carry out sample approbation of calculations, and evaluate results. The article considers these issues in relation to specific regions.